Formation of Gel-like Nanodomains in Cholesterol-Containing Sphingomyelin or Phosphatidylcholine Binary Membrane As Examined by Fluorescence Lifetimes and 2H NMR Spectra - Yasuda, Tomokazu; Matsumori, Nobuaki; Tsuchikawa, Hiroshi; Lönnfors, Max; Nyholm, Thomas K. M.; Slotte, J. Peter; Murata, Michio (Langmuir, 2015)
In this study, we measured the time-resolved fluorescence of trans-parinaric acid (tPA), steady-state fluorescence anisotropy of diphenylhexatriene (DPH), and 2H NMR of 10,10-d 2-stearoyl lipids in stearoyl sphingomyelin with cholesterol (SSM/Chol) and l-palmitoyl-2-stearoyl-sn-glycero-3-phosphocholine with Chol (PSPC/Chol) binary membranes. The results suggest that the membrane order obtained from the fluorescence experiments shows a similar temperature dependency as those of the 2H NMR data. More importantly, the time-resolved fluorescence data implied the presence of at least two types of domains, cholesterol-poor gel-like domains (CPGLD) and cholesterol-enriched liquid-ordered (Lo) domains. These domains appear on a nano-to-micro second time scale for both SSM-Chol and PSPC-Chol membranes. The relative size of the gel-like domain was also estimated from the temperature-dependent lifetime measurements and 2H NMR spectral changes. The results imply that the size of the gel-like domains is very small, probably on the nanometer scale, and smaller in SSM-Chol membrane than those in PSPC-Chol bilayers, which could account for the higher thermal stability of SM-Chol membranes. The present study demonstrates that gel-like nanodomains occur in SM-Chol binary membrane even with Chol content of over 33 mol %, which has been thought to consist exclusively of Lo phase, implying that not only Lo domains but also gel-like nanodomains are important for formation of lipid-ordered phase in SM-Chol and PC-Chol membranes.